2019
DOI: 10.1029/2018ja026443
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Periodic Wave‐like Structures in the Ionosphere Observed at Low Latitudes over the Asian‐Australian Sector Using Total Electron Content from Beidou Geostationary Satellites

Abstract: Daytime periodic wave-like structures are statistically analyzed for the first time in the low-latitude ionosphere over the Asian-Australian sector using total electron content from Beidou geostationary satellites during 2016-2017. These structures have periods of about 18-28 min, which frequently occur during 11:00-17:00 local time in the winter at latitudes ranging between 17 and 25°N (10-18°N magnetic latitude [MLAT]) in the Northern Hemisphere, where they have a maximum occurrence rate of 80% at~21°N (14°N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…To study the ionospheric responses to the August 2018 geomagnetic storm, multiple ionospheric data sets are collected including: (1) the Beidou GEO TECs with 30‐s time resolution from 15 receivers at the Asian‐Australian sector (near 110°E) (Huang et al, 2019); (2) the Global Navigation Satellite System (GNSS) TECs provided by the MIT Haystack Observatory at a 5 min and 1° × 1° (latitude × longitude) resolution over the American (70°W) and the African (40°E) longitudinal sectors (Rideout & Coster, 2006); (3) the electron density ( Ne ) profiles from ionosondes at Wuhan (24.4°N magnetic latitude), Shaoyang (21.0°N magnetic latitude), Sanya (11.6°N magnetic latitude), Jicamarca (0.1°N magnetic latitude), and Cachoeira Paulista (18.8°S magnetic latitude). The location information about the stations of Beidou GEO TEC and ionosondes is listed in Table 1, and their distributions are shown in the map of Figure 2.…”
Section: Data Setmentioning
confidence: 99%
“…To study the ionospheric responses to the August 2018 geomagnetic storm, multiple ionospheric data sets are collected including: (1) the Beidou GEO TECs with 30‐s time resolution from 15 receivers at the Asian‐Australian sector (near 110°E) (Huang et al, 2019); (2) the Global Navigation Satellite System (GNSS) TECs provided by the MIT Haystack Observatory at a 5 min and 1° × 1° (latitude × longitude) resolution over the American (70°W) and the African (40°E) longitudinal sectors (Rideout & Coster, 2006); (3) the electron density ( Ne ) profiles from ionosondes at Wuhan (24.4°N magnetic latitude), Shaoyang (21.0°N magnetic latitude), Sanya (11.6°N magnetic latitude), Jicamarca (0.1°N magnetic latitude), and Cachoeira Paulista (18.8°S magnetic latitude). The location information about the stations of Beidou GEO TEC and ionosondes is listed in Table 1, and their distributions are shown in the map of Figure 2.…”
Section: Data Setmentioning
confidence: 99%
“…These different features of TIDs were related to different mechanisms. More recently, Huang et al (2019) reported a peak occurrence of daytime TID at ~21°N over the low‐latitude region of Asian‐Australian sector. The potential sources and generation mechanisms still remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Beidou GEO TEC data with a time resolution of 30 s from 15 GNSS receiver stations were used. The Beidou GEO TEC can provide ionospheric observations along fixed paths since ionospheric pierce points (IPPs) almost do not move (Huang et al, 2017(Huang et al, , 2018(Huang et al, , 2019. Thus, it gives a high-fidelity observation to detect the ionospheric variations, for instance, the changes induced by the eclipse.…”
Section: Data Descriptionmentioning
confidence: 99%